Development of Mathematical Maturity through the Amalgamation of Computational Thinking and Technology-Enhanced Learning - Prabawa, Harsa Wara; Rosjanuardi, Rizky; Nurlaelah, Elah (JTAM (Jurnal Teori dan Aplikasi Matematika), 2024)
Advancements in technology and global information infrastructure have transformed education, leveraging a constructivist approach that enhances knowledge construction through student interaction with computer applications. The research aimed to explore the facilitation of enhancing mathematical maturity through the integration of technology in mathematics education using computational thinking. This research employed a qualitative method with a case study approach. The participants in this study were 15 Grade XI students from various classes of the Vocational High School, selected from a total of 159 students. The data collection techniques used in this research included observation and open-ended test instruments. The data analysis techniques involved data reduction, data presentation, and conclusion drawing. The research results show: (1) technology enhances mathematics education; (2) computers deepen mathematical understanding; (3) technology creates contextual learning environments for problem-solving; (4) combining computational thinking and technology aids in mastering mathematical concepts. The conclusion is that integrating computational thinking with technology-enhanced learning significantly fosters mathematical maturity among students.